The Effect of Read Loud Learning on the Ability to Read the Yellow Book : English - Almannah Wassalwa; Shofwatul Fu'adah (JOEY: Journal of English Ibrahimy, 2023)
Reading the yellow book is no longer a new thing in the world of Islamic boarding schools. Each Pesantren has different standards. Likewise in every institution that exists in the pesantren itself, especially in our Pesantren. Students are expected not only to be able to read the yellow book. However, they are also expected to understand the yellow book they are reading. And can really understand the rules of syntax and morphemes. The ability to read the yellow book for class IV intensive MQ girls, especially for Maharoh Qiro'ah, is a key or central problem that must be taken seriously so that students are able to read the book well. As well as being required to study the science of tools related to the yellow book such as the nahwu-short rule. One of the causes of student difficulties is the difference in previous educational backgrounds. Especially, graduates who have never known tool science before. Therefore, educators here need a few ways to make delivery more concise and easy to understand and to be able to find out what the effect of this method is.